DAKWAH LESBUMI NU: SAPTAWIKRAMA - Asmar, Afidatul (JURNAL ISLAM NUSANTARA, 2020)
In conceptually, da'wah can be interpreted as an effort to invite, bring and move people to achieve better conditions. Da'wah can be interpreted as gathering people in goodness and showing them to the right path by way of amar ma'ruf nahi munkar. This can occur because of the precise preaching planning and strategy carried out by true Islamic fighters (our predecessors) in remodel a society without causing prolonged horizontal conflict. So the society know that Islam is friendly, tolerant, and full of peace religion. In the assessment, we will be a central place to the problems of society and life. We do not hold to the motto "word for word, poem for poem". We don’t want to let go of poetry from its social and communicative functions. It is natural for an artist to create his work based on concrete problems caused by the tensions of the community. The important thing is the personal style of the artist used to express something for the public. This paper aims to describe the cultural concept of LESBUMI NU with the Saptawikrama strategy.